ID 258 – Defective motor cortex plasticity in juvenile myoclonic epilepsy. Issue 3 (March 2016) - Pizzamiglio, C.; Strigaro, G.; Falletta, L.; Matino, E.; Tondo, G.; Varrasi, C.; Cantello, R.
Abstract : Objective: Abnormal cortical plasticity has been hypothesized to play a crucial role in the pathogenesis of juvenile myoclonic epilepsy (JME). To study the motor cortical plasticity we used paired associative stimulation (PAS). When a repetitive electrical stimulus to the median nerve is paired with a transcranial magnetic stimulus (TMS) pulse over the controlateral motor cortex with at an interstimulus interval (ISI) of 25 ms, a long-term potentiation (LTP)-like synaptic plasticity is induced in the corticospinal system. Aim of this study was to investigate the motor cortex LTP-like synaptic plasticity by means of PAS in patients with JME. Methods: Twelve adult patients with JME were compared with 13 healthy subjects of similar age and sex. PAS consisted of 180 electrical stimuli of the right median nerve paired with a single TMS over the hotspot of right APB at ISI of 25 ms (PAS25). We measured motor evoked potentials (MEPs) before and after each intervention for up to 30 min. Results: In healthy subjects the PAS25 protocol was followed by a significant increase of MEP amplitude. On the contrary, in patients with JME, the MEP amplitude did not change. Conclusions: Defective motor cortex plasticity may be involved in the pathogenesis of JME.